Pengaruh Dosis Pupuk Organik Cair Dari Urin Kelinci dan Macam Varietas Terhadap Pertumbuhan dan Hasil Tanaman Bayam Merah (Alternanthera amonea.Voss) - Yoga Gumelar; Junaidi Junaidi; Tjatur Prijo Rahardjo (JINTAN : Jurnal Ilmiah Pertanian Nasional, 2022)
This study aimed to determine the effect of the dose of liquid organic fertilizer in rabbit urine on the growth and yield of three varieties of red spinach. This research was conducted in Watulimo Village, Watulimo District, Trenggalek Regency at an altitude of 154 meters above sea level from August 23 to October 15, 2021. The study used a two-factor Completely Randomized Design (CRD) which was repeated 3 times, namely: First factor: Dosage of rabbit urine (U) which consisted of 3 treatments, repeated 3 times, namely: U0 = Without fertilizer U1 = dose of rabbit urine 60 ml/plant U2 = dose of rabbit urine 120 ml/plant, Second factor: Red spinach variety (V) which consisted of 3 treatments repeated 3 times, namely: V1 = Mira variety, V2 = Clara variety, V3 = Variety BA-285. From the results of the research that has been carried out, it can be concluded that there was a very significant interaction between doses of rabbit urine and red spinach varieties on plant height at age 14; 21; 28; and 35 days after planting, wet weight per plant and dry weight per plant at harvest time for the best results from the combination of U2V3 treatments. The treatment dose of rabbit urine was significantly different to plant height at 7 DAP, the number of leaves at observation age at 7 DAP, 14 DAP, 21 DAP, 28 DAP, 35 DAP the largest yield was U2, (rabbit urine dose 120 ml/plant). The treatment of varieties of red spinach was significantly different to plant height at 7 DAP, the number of leaves at the observation age at 7 DAP, 14 DAP, 21 DAP, 28 DAP, 35 DAP, and the largest yield was V2, (red spinach variety BA285).